Peran Dan Orientasi Pemda Dalam Mengoptimalisasi Pendapatan Asli Daerah (Studi Kasus Badan Pendapatan Daerah Kabupaten Sukabumi) - Cristina, Nadia (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2022)
This research was conducted to determine the Role and Orientation of Provincial Government in optimizing the Original Income of the Regional Revenues Agency (BAPENDA) of Sukabumi Regency, where there are roles and orientation that can help increase their source of income, including Regional Taxation, Regional Management, Result of Wealth Management of Other regions and Original Revenue and Orientation in Regions (BAPENDA). The research method used is a qualitative method with a descriptive approach. In qualitative research does not use population term, but is called a social situation including the place, perpetrator and activity, and sample in qualitative research is not called respondents but sources or informant. The population in this study is the place of research is the Regional Revenues Agency (BAPENDA) of Sukabumi Regency, the perpetrator in this study is Head of Areas or Secretary at the Regional Revenues Agency (BAPENDA) of Sukabumi Regency, and the activity that occurred is doing research regarding the orientation and role of the Sukabumi Regency. The samples used in this study were only information, PAD data and documentation through an interview with Head of Sector. Based on the result of the study that have been carried out, it can be know that the role and orientation of Pemda at the Regional Revenues (BAPENDA) of Sukabumi Regency. Sukabumi Revenue District and His region was already exceeded and above average.